Pengambilan Keputusan Penentuan Target Promosi Universitas menggunakan metode Analytical Hierarchy Process - Aldi Bastiatul Fawait; Sitti Rahmah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Decision-making in determining promotion targets becomes crucial for Widya Gama Mahakam University in Samarinda City to enhance the institution's visibility and attractiveness. The Analytical Hierarchy Process (AHP) method is proposed as an effective approach. The issues faced include difficulties in determining effective and efficient promotion target priorities and a lack of strong scientific foundations to support strategic decision-making. The proposed solution is to implement AHP as a structured and systematic decision-making tool. This method allows the identification of relevant criteria and determination of relative weights for each criterion, then evaluating and selecting the best alternatives. This research involves the analysis of various relevant promotion aspects, such as Type of high school, Distance, Transportation, School accreditation, and Number of alumni as criteria for High School (SMA) that will be used. The main objective is to identify relevant criteria in determining promotional targets, assess the relative weights of each criterion, and generate priorities or rankings of promotional targets based on AHP analysis. The findings of the research demonstrate a consistency ratio of 0.0852, which falls below 0.1, indicating its proper interpretation according to the CR calculation theory within the AHP methodology, thus considered appropriate for application. This research produces a ranking of promotion target determination for Widya Gama Mahakam University in Samarinda City, with alternative A5 ranking first, alternative A7 ranking second, A3 ranking third, A4 ranking fourth, A1 ranking fifth, A10 ranking sixth, A9 ranking seventh, A8 ranking eighth, A2 ranking ninth, and A6 ranking tenth. The research findings indicate the AHP method can be utilized for decision-making within establishing promotion targets for Widya Gama Mahakam University in Samarinda City